Hypoxia-induced shedding of MICA and HIF1A-mediated immune escape of pancreatic cancer cells from NK cells: role of circ_0000977/miR-153 axis - Ou, Zheng-Lin; Luo, Zhen; Wei, Wei; Liang, Shuai; Gao, Tai-Long; Lu, Ye-Bin (RNA biology, 2019)
One key to malignant progression of pancreatic cancer (PC) is the acquired ability of tumour cells to escape immune-mediated lysis. Hypoxic microenvironment plays a causal role in PC metastasis. According to previous studies, hypoxia could induce the upregulation of HIF1A, ADAM10 and sMICA, leading to decreased NKG2D in NK cells and tumour cells escape from immune surveillance and NK cell-mediated lysis. In the present study, in NK cells derived from high-HIF1A expression patients, the levels of internalization of MICA/B and NKG2D were obviously higher than those in low-HIF1A expression group; hypoxia dramatically upregulated the levels of sMICA culture supernatant of Panc-1 cells. Regarding the molecular mechanism, dysregulated circRNAs and miRNAs that might modulate HIF1A-mediated immune escape were selected and examined for detailed functions. The expression of circ_0000977 could be induced by hypoxia, and circ_0000977 knockdown enhanced the killing effect of NK cells on PC cells under hypoxia through HIF1A and ADAM10. HIF1 and ADAM10 were direct downstream targets of miR-153; circ_0000977 served as a sponge for miR-153 to counteract miR-153-mediated repression of HIF1 and ADAM10 mRNA through direct targeting in both 293T cells and Panc-1 cells. miR-153 inhibition exerted an opposing effect on HIF1A-mediated immune escape of PC cells to circ_0000977 knockdown; the effect of circ_0000977 knockdown were partially attenuated by miR-153 inhibition. In summary, circ_0000977/miR-153 axis modulates HIF1A-mediated immune escape of PC cells through miR-153 downstream targets HIF1A and ADAM10. We provided a novel mechanism of HIF1A-mediated immune escape of PC cells from the perspective of circRNAs-miRNA-mRNA axis. Abbreviations: Pancreatic cancer (PC); peripheral blood lymphocytes (PBLs); A Disintegrin and Metalloproteinase Domain 10 (ADAM10); MHC class I-related molecule A (MICA); soluble MICA (sMICA); membrane MICA (mMICA); Hypoxia-inducible factor 1-alpha (HI1FA); long non-coding RNAs (lncRNAs); non-coding RNAs (ncRNAs); natural killer (NK); Haematoxylin and eosin (H&E); Immunohistochemistry (IHC); natural killer group 2 member D (NKG2D);